2005
DOI: 10.1016/j.jalgebra.2004.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Crossed product conditions for division algebras of prime power degree

Abstract: Let D be an F -central division algebra of degree p r , p a prime. A set of criteria is given for D to be a crossed product in terms of irreducible soluble or abelian-by-finite subgroups of the multiplicative group D * of D. Using the Amitsur's classification of finite subgroups of D * and the Tits alternative, it is shown that D is a crossed product if and only if D * contains an irreducible soluble subgroup. Further criteria are also presented in terms of irreducible abelian-by-finite subgroups and irreducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We remark that the last result generalizes the case where the degree of D is a prime power, which is dealt with in [4]. Let G be an irreducible soluble subgroup of D * .…”
Section: Case 6 Finite Groupsmentioning
confidence: 78%
See 1 more Smart Citation
“…We remark that the last result generalizes the case where the degree of D is a prime power, which is dealt with in [4]. Let G be an irreducible soluble subgroup of D * .…”
Section: Case 6 Finite Groupsmentioning
confidence: 78%
“…In [4] and [10], the authors ask whether a division algebra generated by a soluble-by-finite irreducible subgroup G is necessarily a crossed product over a maximal subfield. For some special cases where D is of a prime power degree and G is soluble or finite, the answer to the above mentioned question is shown to be positive.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], it was proved that if G is soluble, then D is a quasi-crossed product division algebra in the sense that it contains a tower of subfields F = Z(D) K ⊆ L such that K/F is Galois, L is a maximal subfield and L/K is an abelian Galois extension. Also, the results of [14] and [47] assert that D is a crossed product division algebra if one of the following conditions holds:…”
Section: Soluble-by-finite Subgroups Of Division Algebrasmentioning
confidence: 99%
“…The first significant result concerning Question 2.5, was obtained in [60] where the author showed that if G is a soluble maximal subgroup (this means that G is a maximal subgroup of D * that is soluble), then the question has a positive answer. Afterwards, this question became the subject of a series of papers including [13], [14], [47] and [45]. In [13], it was proved that if G is soluble, then D is a quasi-crossed product division algebra in the sense that it contains a tower of subfields F = Z(D) K ⊆ L such that K/F is Galois, L is a maximal subfield and L/K is an abelian Galois extension.…”
Section: Theorem 24 ([69]mentioning
confidence: 99%